Survey of job dimensions and professional requirements of special librarians in Metropolitan Manila - Barnachea, Lutgarda Amor D.; Valera, Jaime B.; Tamesis, Angelina R. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1989)
This study aimed to conduct a survey of the job dimensions and professional requirements of special librarians. Respondents were 51 librarians working in different types of special libraries located in Metropolitan Manila. The instrument used in the study is a questionnaire which asked for the following information: personal and career information, job activities performed in terms of time and importance, and professional needs of librarians. Analysis of data used frequency counts, sums, products, percentages and ranking.
Results indicated that special librarians perform various professional job activities which may be categorized as both library and administrative / management functions. As such they are generalists and this is attributed to the generally small size of staff of the libraries they manage. Library functions, rather than administrative or management, are their most time-consuming activities; at the same time they are perceived to be the most important. The major tasks of special librarians regardless of their position classifications are grouped in the areas of cataloging and classification, circulation, clientele services, and reference. Acquisition counts among the major duties of library administrators who also perform general administrative/management activities that include planning, directing, controlling, housing and representing.
Special librarians desire to undertake continuing professional advancements mainly through workshops, although they desire to take a few areas of study in formal courses. Desired areas of study are those which would enhance the effectiveness in doing their present jobs. The librarians are also interested in courses that will update them on technological trends. Likewise, they are interested to undertake graduate courses both in library science and other subject areas related to their work. Library schools and library associations are therefore urged to provide various opportunities for professional advancement.
Expanding the scope of the present study will provide a more holistic view in determining the professional requirements of librarians in the Philippines. There is an urgent call to pursue vigorously the passage of the Bill on the Professionalization of Librarians. This will ensure certification, so that only those qualified would be allowed to practice the profession of librarianship.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Libraries, Special--Philippines--Metropolitan Manila; Library surveys--Philippines--Metro Manila; Special librarians--Job descriptions